Brill's companion to the classics, Fascist Italy and Nazi Germany - Roche, Helen; Dēmētriou, Kyriakos N. (Brill's companions to classical reception, 2018)
Front Matter -- “Distant Models”? Italian Fascism, National Socialism, and the Lure of the Classics /Helen Roche -- The Aryans: Ideology and Historiographical Narrative Types in the Nineteenth and Early Twentieth Centuries /Felix Wiedemann -- Desired Bodies: Leni Riefenstahl’s Olympia, Aryan Masculinity and the Classical Body /Daniel Wildmann -- Ancient Historians and Fascism: How to React Intellectually to Totalitarianism (or Not) /Dino Piovan -- Philology in Exile: Adorno, Auerbach, and Klemperer /James I. Porter -- Fascist Modernity, Religion, and the Myth of Rome /Jan Nelis -- Bathing in the Spirit of Eternal Rome: The Mostra Augustea della Romanità /Joshua Arthurs -- “May a Ray from Hellas Shine upon Us”: Plato in the George-Circle /Stefan Rebenich -- An Antique Echo: Plato and the Nazis /Alan Kim -- Classics and Education in the Third Reich: Die Alten Sprachen and the Nazification of Latin- and Greek-Teaching in Secondary Schools /Helen Roche -- Classical Antiquity, Cinema and Propaganda /Arthur J. Pomeroy -- Classical Archaeology in Nazi Germany /Stefan Altekamp -- Building the Image of Power: Images of Romanità in the Civic Architecture of Fascist Italy /Flavia Marcello -- Forma urbis Mussolinii: Vision and Rhetoric in the Designs for Fascist Rome /Flavia Marcello -- National Socialism, Classicism, and Architecture /Iain Boyd Whyte -- Neoclassical Form and the Construction of Power in Fascist Italy and Nazi Germany /James J. Fortuna -- Indexes.